Macroeconomic Variables and Stock Returns: Empirical Evidence from Nigerian Stock Market - Adenike, Azeez Aminat (2009)
This study examines the relationships between stock returns and macroeconomic variables in an emerging stock market of the Nigerian stock exchange (NSE); using quarterly data on five macroeconomic variables; exchange rate, consumer price index, industrial production index, lending rate and deposit rate, and the All Share Price Index (ASPI) of the NSE for the period January 1985 to December, 2007. In the empirical analysis, Augmented Dickey-Fuller and Phillip Perron unit root test was employed to test for the stationarity of the data. The result of Engle-Granger and Johansen‟s cointegration test, error-correction models, variance decomposition and impulse response analyses indicate that there are both short and long-run relationships between stock returns and macroeconomic variables in Nigeria. Furthermore, stock return responds positively to consumer price index, deposit rate and industrial price index; and negatively to lending rate and exchange rate. These results indicate that information contained in macroeconomic variables can be used to predict stock returns and hence violate the validity of the semi-strong version of the market efficiency. Although the findings of this research indicate that the Nigerian stock market is not efficient in the semi-strong form of market efficiency, the result is subject to the limitations highlighted in the study. The inefficiency of the NSE could be due to lack of sound macroeconomic policies as a result of frequent changes in government policy and also lack of communication infrastructure.